Estimation of Pesticide Concentrations from Agricultural Land in Cangkringan and Pakem Subdistricts on Runoff in the Upper Opak Watershed - Andriana Eikintawarna; Suphia Rahmawati; Adam Rus Nugroho; Widodo Brontowiyono (Indonesian Society of Limnology, 2024)
Agricultural activities in the Opak Watershed, especially in the upper part located in Sleman Regency, require special attention because they have the potential to have a negative impact on river water quality. The use of pesticides on agricultural land contributes to polluting river water through rainwater runoff. Runoff containing residual organophosphate pesticide residues will reduce river water quality. In order to prevent pesticide pollution in the Upper Opak Watershed (UOW) in a sustainable manner, effective management is needed. However, the lack of information regarding estimates of pesticide concentrations in runoff in the UOW could hamper the management process. Therefore, it is crucial to estimate pesticide concentrations from agricultural land in the Cangkringan and Pakem Subdistricts contained in runoff in the UOW. Estimation of pesticide concentrations in runoff can be done by conducting hydrological modeling. The Soil Conservation Service-Curve Number (SCS-CN) model is the simplest compared to other models, but this model needs to be combined with the Predicted Environmental Concentrations (PEC) model to be able to estimate pesticide concentrations contained in runoff in the UOW. The research results show that the Cangkringan Subdistrict is the larger contributor to the concentration of organophosphate pesticides in the runoff of the UOW. The runoff contains three types of active pesticide substances, with the highest concentration in the two subdistricts being the active substance Diazinon. Active pesticide substances from rice fields in Pakem Subdistrict did not contribute too much to the pesticide pollution on the UOW runoff. Most of the pesticide concentrations in the UOW runoff came from agricultural land.